BS EN IEC 62153-4-16. Metallic cables and other passive components test methods. Part 4-16. Electromagnetic compatibility (EMC). Extension of the frequency range to higher frequencies for transfer impedance and to lower frequencies for screening attenuation measurements using the triaxial set-up (29th August 2019) - British Standards Institution,
No abstract available